Experimental and Numerical Study of Enlarged-Head Monopile Under Lateral Load in Soft Clay - Elsiragy, Mohamed; Azzam, Waseim; Kassem, Engy M. (Civil Engineering Journal, 2025)
The behavior of piles and the reaction of soils in contact with structures are crucial aspects of foundation engineering. Laboratory model tests were investigated to evaluate the enhancement of the subgrade modulus for laterally loaded piles with enlarged heads in clay. These tests compared typical piles with enlarged heads in soft clay, considering factors such as the pile slenderness ratio and geometric configurations. The study was expanded by simulating monopiles with and without head enlargements using the numerical program Plaxis 3D. The results highlight the effectiveness of enlarged-head piles, demonstrating a substantial increase in lateral subgrade reaction with adequate head depth. For piles with Lp/Dp = 24, an enlarged head geometry of Le/Lp = 0.4, Δ De/Dp = 1, and an undrained shear strength Cu = 15, the subgrade modulus improved by 200% compared to typical piles. Additionally, for Lp/Dp = 24 piles, the improvement due to enlargement was 1.3 and 2 times for Cu values of 10 and 15 kPa, respectively. These findings emphasize the advantages of using enlarged heads, especially uniform shapes, which are more practical and effective than tapered shapes. The numerical simulations corroborated the experimental results, providing detailed insights into deformation and bending moment variations that are challenging to measure in laboratory tests. Doi: 10.28991/CEJ-2025-011-02-04 Full Text: PDF